Successful Treatment of Infection of the Vascular Prosthesis Used in Redo Axillo-Bifemoral Bypass Using Aorto-Bifemoral Bypass and Vacuum-Assisted Closure Therapy in a Compromised Patient - Nakamichi, Tsukasa; Mihara, Wahei; Tsunoda, Yu (Japanese Journal of Vascular Surgery, 2012)
Treatment of infection of vascular prostheses implanted during redo axillo-bifemoral bypass is very difficult, especially in compromised patients, because an alternative bypass route has to be made and the infected prosthesis has to be removed completely. We present the case of a 79-year-old man with diabetes mellitus and chronic renal failure who was on hemodialysis, and who underwent a redo axillo-bifemoral bypass 3 months before presentation: Sepsis due to vascular prosthesis infection was diagnosed. Through median sternotomy an extra-anatomic bypass between the ascending aorta and both femoral arteries were performed, and most of the infected vascular prosthesis was removed. We used vacuum-assisted closure therapy on the infected wound. Sixty-seven days after the operation, the infected wound healed completely. Our experience confirms the safety and effectiveness of this treatment option, especially for redo operations in compromised patients.